Prevalence of Hospital Malnutrition at Admission and Outcomes in Pediatric Patients - Sukhosa, Onwaree; Kittisakmontri, Kulnipa (International Journal of Child Health and Nutrition, 2017)
Background: Hospitalized children are at risk of malnutrition and vulnerable for many adverse outcomes. Objectives: This study aimed to determine the prevalence of hospital malnutrition in pediatric patients admitted at Chiang Mai University (CMU) hospital and evaluate correlation between malnutrition and outcomes including length of hospital stay (LOS), total hospital cost and mortality. Methods and Study Design: A prospective cohort study was conducted at CMU hospital. Patients aged 1 month to 15 year-old who admitted to general pediatric wards were included. Demographic data, anthropometric assessments including weight, length/height and outcomes were collected. Malnutrition was classified by the WHO growth reference. Results: A total of 217 patients with mean age 68.8 ± 53.8 month-old were analyzed. Majority of them were male (65.4%) while leading diagnosis were oncologic, infectious and congenital heart diseases. The prevalence of all malnutrition was 59.9%. According to the WHO classification, percentages of the patients who were stunted, wasted, both of stunted and wasted, and overweight were 29.9%, 9.2%, 17.1%, and 3.7%, respectively. Moreover, compared to previous study of this center in 1985, more than half of hospitalized children have still assessed as under-malnourished patients. For the hospital outcomes, wasting regardless of stunting had significantly longer LOS (8 vs 5 days, p = 0.001) and higher hospital expenditure (37,283.0 vs 23,630.0 Baht, p = 0.004) while mortality was not different. Conclusions: The prevalence of malnutrition in hospitalized children is common and remains unchanged. Acute malnutrition significantly impact on total hospital cost and prolong LOS comparing with other groups.